In Silico Approach for Identification of PI3K/mTOR Dual Inhibitors for Multiple Myeloma Treatment - İlke Maşalacı; Yaren Akdoğan; Özge Mutlu; Hande Eyvaz; Yağmur Kiraz (European Journal of Biology)
Objective: Multiple myeloma is a hematologic malignancy in which targeting phosphoinositide 3 kinase (PI3K) and/or the mammalian target of rapamycin (mTOR) individually has been shown to have anti-proliferative effects, however, inhibiting both proteins simultaneously has been reported to have more effective results for its treatment. The aim of this study is to determine the molecular interactions and predicted inhibitory effects of 40 different dual inhibitors on mTOR, PI3Kδ, and PI3Kγ to propose potentially the most effective dual inhibitor that targets the PI3Kδ and PI3Kγ isoforms as well as the mTOR proteins since those isoforms are known to be predominant in multiple myeloma patients. Therefore, the focus in this study is built around the specific targeting of the PI3Kδ and PI3Kγ isoforms from the multiple myeloma perspective. Materials and Methods: In silico docking experiments were conducted to determine the binding energies for different ligands that target mTOR, PI3Kδ, and PI3Kγ. Protein-dual inhibitor complexes and the amino acids and bond types were visualized to identify molecular interactions. The absorption, distribution, metabolism, and excretion properties of dual inhibitors were analyzed and evaluated. Results: The binding affinity values were found to be between -7 and -9.9 kcal/mol. The toxicity prediction values of the selected dual inhibitors were obtained from the Pro-Tox-II web tool and classified according to the globally harmonized system of classification of labeling of chemicals. Conclusion: Correspondingly, among all dual inhibitors, Vistusertib is determined to be a promising compound against multiple myeloma cells by inhibiting both PI3Kδ and PI3Kγ as well as mTORC1/2.